Antioxidant-Loaded Mesoporous Silica—An Evaluation of the Physicochemical Properties - Adrian Szewczyk; Joanna Brzezińska-Rojek; Justyna Ośko; Dorota Majda; Magdalena Prokopowicz; Małgorzata Grembecka (Antioxidants, 2022)
The dangerous effects of oxidative stress can be alleviated by antioxidants—substances with the ability to prevent damage caused by reactive oxygen species. The adsorption of antioxidants onto nanocarriers is a well-known method that might protect them against rough environ-mental conditions. The aim of this study was to investigate the adsorption and desorption of gallic acid (GA), protocatechuic acid (PCA), chlorogenic acid (CGA), and 4-hydroxybenzoic acid (4-HBA) using commercially available mesoporous silica materials (MSMs), both parent (i.e., SBA-15 and MCM-41) and surface functionalized (i.e., SBA-NH2 and SBA-SH). The MSMs loaded with active compounds were characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), thermoporometry (TPM), and powder X-ray diffraction (XRD). High-performance liquid chromatography (HPLC-CAD) was used to evaluate the performance of the adsorption and desorption processes. The antioxidant potential was investigated using the Folin–Ciocalteu (FC) spectrophotometric method. Among the studied MSMs, the highest adsorption of GA was observed for amine-modified SBA-15 mesoporous silica. The adsorption capacity of SBA-NH2 increased in the order of PCA, 4-HBA < GA < CGA. Different desorption effectiveness levels of the adsorbed compounds were observed with the antioxidant capacity preserved for all investigated compounds.